The Role Of The United Nations Population Fund (UNFPA) Through The Implementation Of The Better Sexual Reproductive Health And Rights For All In Indonesia (Berani) Program In Fulfilling Children's Sexual and Reproductive Health Rights - I Wayan Aditya Harikesa; Camellia Nur Sabrina (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
This study aims to analyze the implementation of the Better Sexual Reproductive Health and Rights for All in Indonesia (BERANI) program as one of the efforts of the United Nations Population Fund (UNFPA) as an international organization in dealing with sexual and reproductive health issues in the first phase of the BERANI program in 2018-2023 which continues to the second phase of the program starting in 2024 until 2027 which is still running today. The case study was conducted in the Central Jakarta area because the area is one of the places where the BERANI program is implemented. The research method used is a qualitative approach with data collection through in-depth interviews with related parties, document analysis, and literature studies. The results of the study show that the BERANI program implemented in Central Jakarta is an effort to play the role of UNFPA in addressing sexual and reproductive health issues in children until they continue into old age. The BERANI program is an effort carried out by UNFPA as a form of assistance in handling sexual and reproductive health issues needed by Indonesia, including the Central Jakarta area. Although challenges still exist, the program provides hope for an increase in the fulfillment of children's sexual and reproductive health rights through education.